PENGARUH KEJELASAN SASARAN ANGGARAN, KOMPETENSI SUMBER DAYA MANUSIA DAN MOTIVASI TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (STUDI EMPIRIS PADA SKPD PEMERINTAH KOTA BUKITTINGGI) - Nadia triwahyuni; Desiyanti Rifayani (Komunitas Manajemen Kompetitif, 2025)
This research aims to obtain empirical evidence in the form of the influence clarity budget targets, human resource competence and motivation on the accountability of government agency performance in Kota Bukittinggi. This research was carried out at Kota Bukittinggi SKPDs which the total number was 30 SKPD with 87 respondents. The technique of collecting data used survey techniques, namely by distributing questionnaires which will be given directly to respondents. The results of this research showed that clarity of budget targets and human resource competence has positive effect on the accountability of government agency performance. Meanwhile, the work motivation variable has no effect on the accountability of government agency performance carried out at the Bukittinggi SKPD.